Study of agricultural economic potential in West Kalimantan using Regional Analysis Techniques - Nurulhuda, S. (EDP Sciences, 2021)
The agricultural resource is one of the most critical sectors in the economy, which contributes a high portion of the growth and development of a particular region. Differences in characteristics and potential between regions give rise to the basic and non-basic sectors, which then affect income contribution. This research aims to analyze the economic potential of the agricultural sector of the regencies and cities in West Kalimantan Province as basic or non-basic sector. Both basic and non-basic sector analysis can be carried out using quantitative-descriptive methods using Shift-Share and Location Quotient (LQ) analysis. The analysis was carried out using secondary data from the Central Statistics Agency (BPS) publication from 2015 to 2020. The results of the LQ analysis show the agricultural sector in Sambas, Bengkayang, Landak, Mempayah, Sanggau, Ketapang, Sintang, Kapuas Hulu, Sekadau, and Kayong Utara are the basic sector. Meanwhile, the agricultural sector in Kubu Raya, Pontianak, and Singkawang are non-basic sector. Agriculture in Melawi Regency has changed from a basic sector in 2015, to a non-basic sector in 2020. The results of the Shift-Share analysis show the agricultural sector in Sambas, Bengkayang, Landak, Mempayah, Sanggau, Ketapang, Kapuas Hulu, Sekadau, Kubu Raya, Pontianak and Singkawang have progressive or advanced growth, while Sintang, Melawi and Kayong Utara have slowed growth. Â© The Authors, published by EDP Sciences.